2014
DOI: 10.3174/ajnr.a3933
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Aneurysmal Flow Diversion Using a Dynamic Push-Pull Technique: An Experimental and Modeling Study

Abstract: BACKGROUND AND PURPOSE: Neurovascular flow diverters are flexible, braided stent-meshes for intracranial aneurysm treatment. We applied the dynamic push-pull technique to manipulate the flow-diverter mesh density at the aneurysm orifice to maximize flow diversion. This study investigated the hemodynamic impact of the dynamic push-pull technique on patient-specific aneurysms by using the developed high-fidelity virtual-stenting computational modeling technique combined with computational fluid dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 13 publications
(21 reference statements)
1
49
0
Order By: Relevance
“…This is of critical importance, because we have previously demonstrated that a single device when packed can result in greater than 50% metal surface coverage, and 2 devices seriously threaten the patency of the critical perforators that are typically crowded around the necks of these aneurysms. 10 By using a single device over perforator segments, we have significantly reduced the occurrence of large, devastating perforator strokes.…”
Section: Number Of Pedsmentioning
confidence: 99%
“…This is of critical importance, because we have previously demonstrated that a single device when packed can result in greater than 50% metal surface coverage, and 2 devices seriously threaten the patency of the critical perforators that are typically crowded around the necks of these aneurysms. 10 By using a single device over perforator segments, we have significantly reduced the occurrence of large, devastating perforator strokes.…”
Section: Number Of Pedsmentioning
confidence: 99%
“…27 Parent vessel diameter measurement and location of aneurysmal flow impingement will help clinicians to better choose and place stents 5,13,21 and flow diverters. 7,17,28 However, calculation of morphometrics and hemodynamics is typically done retrospectively away from the interventional suite, and it typically requires welltrained engineers/researchers to perform image-based modeling based on existing methods. In developing AView, we have sought the input of neurosurgeons and neurointerventionalists as the main source for workflow design and system specifications, with the aim of hiding the engineering complexity with an intuitive interface and minimal user interaction.…”
Section: Discussionmentioning
confidence: 99%
“…4). 15) This is expected to promote thrombus formation. Also, the possibility that persistence of a jet flow is involved in delayed rupture has been proposed, and the risk of delayed rupture may be reduced if the jet flow can be controlled by such a placement method.…”
Section: Effects Of the Procedures Of Fd Placement On Cfdmentioning
confidence: 99%